Critical questions in diabetes management: What are the most compelling challenges and how can we handle them? - Alper Sonmez; Cem Haymana; Ibrahim Demirci; Mustafa Cesur; Manfredi Rizzo; Ilker Tasci (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2022)
Background: The prevalence of diabetes mellitus is growing worldwide, showing almost a 10-fold increase in the last five decades. Despite advances in the understanding of the disease mechanisms, preventive measures, and treatment options, morbidity and mortality remain high. Moreover, the burden of uncontrolled glycemia and associated complications have a significant impact on healthcare costs. To be ready for the future and emerging issues in the management of diabetes and related disorders, a holistic approach is essential for the prevention of the next generations. So many challenges in the management of diabetes exist globally, which differ according to the health infrastructure, and cultural, economic, and sociodemographic status of the nations. Conclusions: In this minireview and commentary on previously unaddressed needs relating to the management of diabetes, we discuss the ubiquitous and most compelling challenges and suggest potential solutions in the care of patients with diabetes.